Molecular signaling in bone cells: regulation of cell differentiation and survival - Plotkin, Lilian I. (Adv Protein Chem Struct Biol, 2019)
The achievement of proper bone mass and architecture, and their maintenance throughout life requires the concerted actions of osteoblasts, the bone forming cells, and osteoclasts, the bone resorbing cells. The differentiation and activity of osteoblasts and osteoclasts are regulated by molecules produced by matrix-embedded osteocytes, as well as by cross-talk between osteoblasts and osteoclasts through secreted factors. In addition, it is likely that direct contact between osteoblast and osteoclast precursors, and the contact of these cells with osteocytes and cells in the bone marrow, also modulate bone cell differentiation and function. With the advancement of molecular and genetic tools, our comprehension of the intracellular signals activated in bone cells has evolved significantly, from early suggestions that osteoblasts and osteoclasts have common precursors and that osteocytes are inert cells in the bone matrix, to the very sophisticated understanding of a network of receptors, ligands, intracellular kinases/phosphatases, transcription factors, and cell-specific genes that are known today. These advances have allowed the design and FDA-approval of new therapies to preserve and increase bone mass and strength in a wide variety of pathological conditions, improving bone health from early childhood to the elderly. We have summarized here the current knowledge on selected intracellular signal pathways activated in osteoblasts, osteocytes, and osteoclasts.